2018
DOI: 10.3390/vibration1010003
|View full text |Cite
|
Sign up to set email alerts
|

The Control of an Active Seat Suspension Using an Optimised Fuzzy Logic Controller, Based on Preview Information from a Full Vehicle Model

Abstract: Abstract:The use of suspension preview information obtained from a quarter vehicle model (QvM) to control an active seat has been shown by the authors to be very promising, in terms of improved ride comfort. However, in reality, a road vehicle will be subjected to disturbances from all four wheels, and therefore the concept of preview enhanced control should be applied to a full vehicle model. In this paper, different preview scenarios are examined, in which suspension data is taken from all or limited axles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In addition, a preview information was obtained from the wheels, front left suspension and front axle, which was optimized by fuzzy logic controller to cope up with friction and actuator constraints [85]. State feedback of the seat suspension and feedforward of the vehicle suspension based on preview information were implemented in [86].…”
Section: Preview Controllermentioning
confidence: 99%
“…In addition, a preview information was obtained from the wheels, front left suspension and front axle, which was optimized by fuzzy logic controller to cope up with friction and actuator constraints [85]. State feedback of the seat suspension and feedforward of the vehicle suspension based on preview information were implemented in [86].…”
Section: Preview Controllermentioning
confidence: 99%
“…The results showed that this approach significantly reduces the vertical vibration at the driver's seat when compared with a passive system. In addition, in a recent simulation based study by the authors [23], this concept was successfully applied to an active seat in a multi-degree of freedom full vehicle model incorporating the roll and pitch modes.…”
Section: Preview Controlmentioning
confidence: 99%
“…They verified that the proposed algorithm could improve the ride comfort and adhesion ability through the simulation analysis of the suspension system. Alfadhli et al [24] used a PSO optimized fuzzy control algorithm to analyze the active seat suspension system, and the simulation results showed the effectiveness of the control method on ride comfort. Phu et al [25] proposed a new adaptive hybrid controller based on H ∞ , sliding mode control, and PID control to control the magnetorheological seat suspension system.…”
Section: Introductionmentioning
confidence: 99%